Catalyst-free synthesis of 2, 3-dihydrobenzofurans through [4+1] cycloaddition of ortho-hydroxyphenylsubstituted para-quinone methides and sulfur ylides. Issue 5 (1st February 2018) - Chen, Xin-Meng; Xie, Ke-Xin; Yue, Deng-Feng; Zhang, Xiao-Mei; Xu, Xiao-Ying; Yuan, Wei-Cheng
Abstract: An efficient [4+1] cycloaddition of ortho -hydroxyphenylsubstituted para- quinone methides and sulfur ylides was achieved under the catalyst-free condition. With this developed protocol, a series of trans -2, 3-dihydrobenzofurans were obtained in excellent yields (up to 99%) with high diastereoselectivities (>20:1 dr). The usefulness of the protocol was also demonstrated by the versatile conversions of the 2, 3-dihydrobenzofurans into other functionalized benzofurans. Graphical abstract: